Optimalisasi Material Strength Properties Timbunan untuk Kestabilan Lereng Timbunan PT Putra Perkasa Abadi, Site Job PT Makmur Lestari Primatama, Kecamatan Langgikima, Kabupaten Konawe Utara, Provinsi Sulawesi Tenggara - Maya Almaniar Zulhi Wibiyana; Yuliadi; Elfida Moralista (Bandung Conference Series: Mining Engineering, 2022)
Abstract. The mining system has the potential for mining water problems that have an impact on the entry of water into the mine openings, thus affecting working conditions with a decrease in rock strength resulting in instability. The mining water problem occurred at PT PPA Site Job PT MLP disposal area and pit. This research was conducted to determine the value of the actual rock strength (strength material), runoff water management in the form of determining the dimensions of the drains, sump dimensions, the number and specifications of the pump to be used, and the value of the safety factor (FK) on the slopes. The research method used is the geotechnical analysis of slope stability with the Finite Element Method and the Limit Equilibrium Method and is simulated with Phase2 and Slide software. The study was conducted in the disposal area divided into 5 sections (A-E). The input material parameters used are the internal shear angle (Ø), cohesion (c) and the density of the embankment material (ɤ) which are obtained based on the results of testing the physical and mechanical properties of the bulk and core samples. Runoff water management is carried out by hydrological analysis using the Gumbel distribution method and the Mononobe equation, while the planning of the dimensions of the water channel uses the Manning formula and the sump dimension by trial and error based on the amount of water discharge entering the pit. The test results show the lowest cohesion (c) value is 0.22 kg/m2 and the lowest internal shear angle (Ø) is 15.30º. Hydrological analysis for recommendations for the dimensions of waterways in the management of runoff water outside the pit, namely the width of the base (B) 0.4 meters; optimal water height (h) 0.21 meters; channel height (H) 0.45 meters and top length (L) 0.90 meters. The dimensions of the sump in the management of runoff and groundwater in the pit are 26 meters long, 19 meters wide and 6 meters high with a volume capacity of 2,964 m3, and the pump used is Multiflo® RF-420EXHV which has specifications with a maximum rotation speed of 1700 rpm, head 250 meters and pumping capability of 450 l/s. Geotechnical analysis in the disposal area shows that section A of the slopes (a) and E and in the area of the pit section Y there is no need for slope geometry recommendations based on KEPMEN 1827K/MEM/30/2018 with a safety factor value (FK) 1,3. Abstrak. Sistem penambangan memiliki potensi permasalahan air tambang yang berdampak dengan masuknya air kedalam bukaan tambang sehingga mempengaruhi kondisi kerja dengan penurunan kekuatan batuan yang mengakibatkan ketidakstabilan. Permasalahan air tambang tersebut terjadi pada PT PPA Site Job PT MLP area disposal dan pit. Penelitian ini dilakukan untuk mengetahui nilai kekuatan batuan (strength material), pengelolaan air limpasan berupa penentuan dimensi saluran air, dimensi sump, jumlah dan spesifikasi pompa yang akan digunakan, serta nilai faktor keamanan (FK) pada lereng. Metode penelitian yang digunakan adalah analisis geoteknik kestabilan lereng dengan metode elemen hingga (Finite Element Method) dan metode kesetimbangan batas (Limit Equilibrium Method) serta disimulasikan dengan software Phase2 dan Slide. Penelitian dilakukan pada area disposal yang dibagi menjadi 5 section (A-E). Input parameter material yang digunakan adalah sudut geser dalam (Ø), kohesi (c) dan berat jenis material timbunan (ɤ) yang diperoleh berdasarkan hasil pengujian sifat fisik dan sifat mekanik pada bulk dan core sample. Pengelolaan air limpasan dilakukan dengan analisis hidrologi menggunakan metode Distribusi Gumbel dan persamaan Mononobe, sedangkan perencanaan dimensi saluran air menggunakan rumus Manning dan dimensi sump dengan trial and error berdasarkan jumlah debit air yang masuk ke dalam pit. Hasil pengujian menunjukkan nilai kohesi (c) terendah sebesar 0,22 kg/m2 dan nilai sudut geser dalam (Ø) terendah sebesar 15,30º. Analisis hidrologi untuk rekomendasi dimensi saluran air dalam pengelolaan air limpasan di luar pit yaitu lebar dasar (B) 0,4 meter; tinggi air optimal (h) 0,21 meter; tinggi saluran (H) 0,45 meter dan panjang atas (L) 0,90 meter. Dimensi sump dalam pengelolaan air limpasan dan air tanah di dalam pit yaitu panjang 26 meter, lebar 19 meter dan tinggi 6 meter dengan kapasitas volume 2.964 m3, serta pompa yang digunakan adalah Multiflo® RF-420EXHV memiliki spesifikasi dengan kecepatan putaran maksimal 1700 rpm, head 250 meter dan kemampuan pemompaan 450 l/s. Analisis geoteknik pada area disposal menunjukkan section A lereng (a) dan E serta pada area pit section Y tidak diperlukannya rekomendasi geometri lereng berdasarkan KEPMEN 1827K/MEM/30/2018 dengan nilai faktor keamanan (FK) ≥ 1,3.